Brittle Culm 15 mutation alters carbohydrate composition, degradation and methanogenesis of rice straw during in vitro ruminal fermentation - Yi, Siyu; Zhang, Xiumin; Zhang, Jianjun; Ma, Zhiyuan; Wang, Rong; Wu, Duanqin; Wei, Zhongshan; Tan, Zhiliang; Zhang, Baocai; Wang, Min (Frontiers in Plant Science, 2022)
Brittle Culm 15 (BC15) gene encodes a membrane-associated chitinase-like protein that participates in cellulose synthesis, and BC15 gene mutation affects cell wall composition in plant. The present study was designed to investigate the changes of carbohydrates composition in bc15 mutant straw, and the resulting consequence on rumen fermentation, methanogenesis, and microbial populations (qPCR) during in vitro ruminal fermentation process. Two substrates, bc15 mutant and wild-type (WT) rice straws, were selected for in vitro rumen batch culture. The first experiment was designed to investigate the kinetics of total gas and CH4 production through 48-h in vitro ruminal fermentation, while the second experiment selected incubation time of 12 and 48 h to represent the early and late stage of in vitro ruminal incubation respectively, and then investigated changes in biodegradation, fermentation end products, and selected representative microbial populations. The bc15 mutant straw had lower contents of cellulose, neutral detergent fiber (NDF) and acid detergent fiber (ADF), and higher contents of water-soluble carbohydrates, neutral detergent solubles (NDS) and monosaccharides. The bc15 mutant straw exhibited a distinct kinetics of 48-h total gas and CH4 production with faster increases in early incubation when compared with WT straw. The bc15 mutant straw had higher DM degradation, NDF degradation and total volatile fatty acid concentration at 12 h of incubation, and lower NDF degradation and CH4 production at 48 h of incubation, together with lower acetate to propionate ratio and ADF degradation and higher butyrate molar percentage and NDS degradation at both incubation times. Furthermore, the bc15 mutant straw resulted in greater 16S gene copies of F. succinogenes, with lower 18S gene copies of fungi at both incubation times. These results indicated that the BC15 gene mutation decreased fibrosis of cell wall of rice straw, enhanced degradation at the early stage of rumen fermentation, and shifts fermentation pattern from acetate to propionate and butyrate production, leading to the decreased volume and fractional rate of CH4 production. Thus, this study modified rice straw by manipulating a cell wall biosynthesis gene and provides a potential strategy to alter degradation and CH4 production during in vitro ruminal fermentation process.